Colonial Heritage and its Impact on the Development of the Algerian Financial System - Kara, Rabah (جامعة علي لونيسي البليدة 2 - كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2018)
الغرض من هذه المقالة هو تقديم ملخص للتطور والتغيرات التي شهدها الاقتصاد والنظام المالي الجزائري خلال الفترة الاستعمارية، وتحليل بالاعتماد على المنهج التاريخي، آثار هذه الفترة على تطور النظام المالي للجزائر، والتي يمكن أن تشكل معالم تاريخية هامة لفهم تطور اقتصاد الجزائر المستقلة، حيث أن الإرث الاستعماري يؤثر حتى اليوم على اتجاه الاقتصاد الجزائري كما توضحه هذه المقالة.
The purpose of this paper is to present a summary of the evolution and changes experienced by the economy and the financial system of Algeria during the colonial period, and to analyze the effects of this period on the development of her financial system, which can constitute a very important references marks for understanding the evolution of economy of independent Algeria seeing that the colonial heritage influences until today the orientation of the economy as illustrated in this paper.
Keywords: الاقتصاد الجزائري -- النظم المالية الجزائرية -- الاقتصاد الاستعماري